Gambaran Hasil Pemeriksaan Keton Urin Segera dan Ditunda Metode Dipstik - Angela Carolina Zebua; Agus Sudrajat (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Laboratory testing is part of a medical process, both from the beginning to the monitoring of diagnostic development, often the urine tested experiences delays due to late delivery of samples or other factors. One element in the urine is the body of ketone (acetoacetate, 3-hydroxybutyrate, and acetone). Acetone includes the classification of ketones with easily evaporating properties due to temperature. Urine ketone is checked by dipstick methods. There's a 10-90% decrease in urine ketone if urine tests are delayed for 2 hours. Of the 30 urine samples with varying results, which are decreasing and increasing but still touch the normal value limit of urine ketone 0.5 mmol/L. Optimal handling and time of urine sampling for urine ketone testing should be observed to maintain medical protocol and ensure more accurate diagnostic results on the public health service network.